2021
DOI: 10.3390/en14051472
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Mapping of a High-Speed Electric Motor Used for Traction Applications and Analysis of Various Cooling Methods—A Review

Abstract: This paper gives a comprehensive review of advanced cooling schemes and their applications to the permanent magnet synchronous motors (PMSMs), as well as investigating the electrical motor’s topologies its thermal design issues, materials and performances. Particularly, the electromagnetic and electric performances, machine sizing, together with the structural design, are given. In addition, the work addresses the motor’s material design and properties along with its insulation performance, which is the main g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…A gearbox is typically used to scale the output torque or speed, but due to the intrinsic nature of electric motors, i.e., their torque and speed characteristics and high overall efficiency contour, EVs are usually equipped with a single-or dual-speed gearbox (Sorniotti et al, 2011). But for battery EVs, there are many options for motors, such as induction motors, switched reluctance motors, and permanent magnet synchronous motors (PMSM) that all belong to the category of AC motors (Gundabattini et al, 2021).…”
Section: Transmission and Motorsmentioning
confidence: 99%
“…A gearbox is typically used to scale the output torque or speed, but due to the intrinsic nature of electric motors, i.e., their torque and speed characteristics and high overall efficiency contour, EVs are usually equipped with a single-or dual-speed gearbox (Sorniotti et al, 2011). But for battery EVs, there are many options for motors, such as induction motors, switched reluctance motors, and permanent magnet synchronous motors (PMSM) that all belong to the category of AC motors (Gundabattini et al, 2021).…”
Section: Transmission and Motorsmentioning
confidence: 99%
“…It has also been observed that most high-power applications of electric motors, such as high-performance cars (e.g., Tesla and Porsche) employ fluid-cooled electric motors It has also been observed that most high-power applications of electric motors, such as high-performance cars (e.g., Tesla and Porsche) employ fluid-cooled electric motors for better cooling efficiency compared to fan cooling, which also takes up space and can lead to overheating. Electric motors are used for various applications ranging from industrial to domestic applications, and induction motors (rotating or linear) are the most used units [7][8][9][10][11]. Water-cooling systems might suffer from leakage issues if not properly designed and maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Various cooling systems for electric motors have been presented in the literature. Among them, the closedloop forced liquid cooling offers the best thermal performance compared to open-or closedloop forced air cooling [2][3][4]. In general, such topologies can be categorized according to the primarily cooled machine part into stator, shaft or end-winding cooling concepts.…”
Section: Introductionmentioning
confidence: 99%